Disruptive innovation, market entry and production flexibility in heterogeneous oligopoly - Chevalier‐Roignant, Benoît; Flath, Christoph M.; Trigeorgis, Lenos (Wiley, 2019)
We develop a model of oligopoly competition involving innovation effort, market entry and production flexibility under demand uncertainty. Several heterogeneous firms make efforts to develop new prototypes; if they succeed, they hold a shared option to enter a new market under stochastic demand. We derive analytic results for the Markov perfect equilibrium accounting for development effort, market entry and production decisions and complement these by numerical analyses. Firm value—which embeds real options—is not convex increasing in demand but exhibits “competitive waves” due to market entries by rivals. A firm with a development advantage (“innovator”) exerts greater innovation effort if the market is a niche, whereas another benefiting from economies of scale (“incumbent”) invests more if the market is larger. Positive externalities benefit the incumbent in the development stage, whereas the innovator is better off in counteracting negative externalities. Demand volatility raises firm incentives to innovate as it enhances the value of firm market‐entry and production flexibility.